ANALISIS ELASTISITAS TRANSMISI HARGA KOPRA DI DESA PONDOS KECAMATAN AMURANG BARAT KABUPATEN MINAHASA SELATAN (Elasticity Analysis of Copra Price Transmission in Pondos Village, Amurang Barat District of South Minahasa Rengency) - Frania Yelfina Mariani Warokka; Grace A. J. Rumagit; Jean F. J. Timban (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to analyze the elasticity of copra transmission prices in Pondos Village, West Amurang District, South Minahasa Regency. Data collection was carried out using a survey method. The data used was time series data, namely, the average price of copra at the farmer level and at the level of collectors for 17 weeks, from the first week of January to the fourth week of April 2021. Based on the results of the study, the elasticity of the transmission of copra prices in Pondos Village, Amurang Barat District, South Minahasa Regency was 0.82. This means that every 1 percent increase in the average price of copra at the collector level will only result in a 0.82 percent change in the average copra price at the farmer level. In other words, the copra marketing system in that place had not been efficient because the market structure was oligopsony.